Associations of pretreatment parameters with changes during orthodontic treatment. (10th May 2019) - Kortam, Sahira; Deguchi, Toru; Geuy, Paul; Johnston, William M.; Fields, Henry W.; Palomo, Juan M.; Kim, Do‐Gyoon
Structured Abstract: Objectives: To examine whether pretreatment conditions of a patient can determine alveolar bone changes after orthodontic treatment. Setting and Sample Population: Cone beam computed tomography (CBCT) images were obtained from 44 patients (17 male and 27 female, 14.02 ± 1.29 years). Material and Methods: Buccal bone height (BBH), buccal bone thickness (BBT), and molar angulation (MA) of right and left maxillary molars and intermolar distance (ID) were measured using the CBCT images obtained before and after orthodontic treatment using conventional brackets and self‐ligating conventional brackets. Results: There was a significant change only in BBH after treatment. All posttreatment parameters had significant positive correlations with the corresponding pretreatment parameters ( r 2 = 0.376‐0.719, P < 0.001). Most of the changes had significant negative correlations with the corresponding pretreatment parameter ( r 2 = 0.054‐0.249, P < 0.03). The results were not significantly influenced by the different bracket types. Conclusion: The current findings suggest that the CBCT‐based morphological information about dentition and oral bone conditions of patients can provide a better pretreatment plan to estimate the results of orthodontic treatment.